A mixed integer programming model for long term capacity expansion planning: A case study from The Hunter Valley Coal Chain - Singh, Gaurav; Sier, David; Ernst, Andreas T.; Gavriliouk, Olena; Oyston, Rob; Giles, Tracey; Welgama, Palitha (European journal of operational research, 2012)
The Hunter Valley Coal Chain is the largest coal export operation in the world with a throughput in excess of 100 million tonnes per annum (Mtpa). Coal is delivered to the shipping terminal from 40 mines using 27 coal load points spread across the Hunter Valley region. This paper describes an MILP model for determining the capacity requirements, and the most cost effective capacity improvement initiatives, to meet demand while minimising the total cost of infrastructure and demurrage. We present results from computational experiments on the model’s performance along with a comparison of the model’s output with detailed analyses by the coal chain analysts and planners.